Analysis Self Efficacy in Improving Work-Life Balance on Employee Performance Terms Sharia Management Perspective - Hardianty, Virnadilla; Hayati, Mardhiyah; Verawati, Heni (Indonesian Journal of Islamic Economics and Finance, 2025)
This study aims to investigate the relationship between Self-Efficacy and Work-Life Balance from the perspective of Islamic management, focusing on employees of the Public Works Department in Bandar Lampung. Employing a qualitative approach, the research involved four employees and utilized techniques such as data collection, reduction, presentation, and conclusion drawing, with data validity ensured through triangulation. The findings reveal that Self-Efficacy acts as a link between Work-Life Balance and employee performance, emphasizing the importance of Islamic management principles that advocate for a balance between personal life and work, as well as between worldly affairs and the hereafter. However, this study has limitations as it was conducted in a single organization with a small sample size, which means that claims regarding the generalizability of the results should be considered with caution. Therefore, the findings of this research are confined to the context of the organization studied. The study also offers practical recommendations for government offices to promote Self-Efficacy and Work-Life Balance, in line with Islamic values that emphasize balance and self-confidence. Overall, this research presents an original approach to understanding employee performance by integrating Self-Efficacy and Work-Life Balance within the framework of Islamic management, highlighting the importance of employees in balancing work responsibilities with personal and family needs.